PENGARUH MANAJEMEN PEMBELAJARAN BERBASIS LINGKUNGAN DAN GAYA KOGNITIF TERHADAP HASIL BELAJAR IPA-FISIKA DI SMPN KOTA BENGKULU (Studi eksperimen pada Siswa Kelas VII Semester I SMPN 11 Kota Bengkulu) 2012 - Nirwana Nirwana (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2014)
The research objectives were to determine the effect of environmental management based learning and cognitive style on learning outcomes of the natural sciences-physics Bengkulu city junior high school students with a sample class VII Semester 1. The experimental group using a managementbased learning environment, while the control group used the conventional learning management. Each group is distinguished by cognitive style field independent and field dependent. The research using experimental methods 2 x 2 factorial design. The research instrument using an objective test of multiple choice and essay limited. By using Anova test hypotheses obtained two lines of research results that the study of the natural sciences-physics students who use learning management environment based higher compared with conventional learning management. Keywords: cognitive style, learning-based environment, conventional.